Determination of Toxic Heavy Metals Present in Jiu River Water using ICP-MS - BARBU, CRISTINA; POPESCU, ALEXANDRU; SELISTEANU, DAN; PREDA, ANISOARA (Asian Journal of Chemistry, 2010)
Heavy metals are natural components of the Earth’s crust. They cannot be degraded or destroyed. As trace elements, some heavy metals (copper, zinc, selenium), are essential to maintain the metabolism of the human body. However, at higher concentrations they can lead to poisoning. Heavy metals poisoning could result from drinking-water contamination (for instance, lead pipes), high ambient air concentrations near emission sources, or intake via the food chain. This paper presents a study of some of the toxic heavy metals distribution on the Jiu river course, an important river in Romania. The most pollutants heavy metals from Jiu river course are lead, mercury and arsenic. The concentration of metals was determined by inductively coupled plasma mass spectrometry.